2020
DOI: 10.1155/2020/7172928
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Static‐Dynamic Tensile Mechanical Properties and Energy Dissipation Characteristic of Limestone Specimen in SHPB Tests

Abstract: To investigate the dynamic splitting tensile mechanical property of limestone under coupled static and dynamic state, the dynamic split tensile tests of limestone under one-dimensional coupled static and dynamic load with different strain rates were performed with the help of modified split Hopkinson pressure bar (SHPB) equipment. The dynamic splitting tensile mechanical property and energy dissipation characteristic under two stress states were also compared in this research. Test results indicated that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…The failure modes of the granite under dynamic splitting can be roughly divided into two types (Figure 14): mode Ⅰ, tensile splitting failure, and mode II, tensile‐shear splitting failure (Mardoukhi et al, 2017; Ping, Fang, et al, 2020). Mode I failure of the BD samples is mainly characterized by a cut‐through main single tensile crack along the loading direction.…”
Section: Test Results and Analysismentioning
confidence: 99%
“…The failure modes of the granite under dynamic splitting can be roughly divided into two types (Figure 14): mode Ⅰ, tensile splitting failure, and mode II, tensile‐shear splitting failure (Mardoukhi et al, 2017; Ping, Fang, et al, 2020). Mode I failure of the BD samples is mainly characterized by a cut‐through main single tensile crack along the loading direction.…”
Section: Test Results and Analysismentioning
confidence: 99%
“…Previous studies have shown that static stress has an important effect on the mechanical properties of rock, such as compressive strength, tensile strength, Poisson's ratio, and Young's modulus [21][22][23]; the static stress controls the evolution of the strain field in rock mass during rock blasting. The strain fields under uniaxial and biaxial static stress are significantly different with those that are under no static stress [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Cheng [6] conducted dynamic experiments on sandstones with different axial pressures to test the energy dissipation of the stress wave and believed that the attenuation of the stress wave energy had a quadratic function relationship with the axial static load. Ping [7] conducted a dynamic splitting test on limestone and believed that the dynamic tensile strength of limestone and the increase in absorbed energy increased as a power function. Ma [8] found through experiments that as the number of prefabricated cracks gradually increased, the energy consumed during the damage and destruction process of the specimen also gradually decreased.…”
Section: Introductionmentioning
confidence: 99%